An efficient link based model for routing, modulation format and spectrum allocation with quality of transmission consideration in elastic optical networks. (2018) - Iyer, Sridhar; Singh, Shree Prakash
Elastic optical networks (EONs) have provision long transmission reach (TR) and high spectral-efficiency (SE). Hence, compared to fixed-grid optical networks, in EONs, managing resources and addressing network design poses complex challenges. In this work, we formulate a link-based mixed integer linear program (MILP) model which considers quality of transmission (QoT) while determining the route, modulation format/level (MF/ML) and spectrum allocation (SA) for every request. To improve SE, model chooses the highest ML; however, when QoT is considered, TR of path with highest ML is very limited. Hence, model finds trade-off between ML, number of required frequency slots (FSs), and TR, with the objective of minimising required amount of network FSs so as to admit all requests. Finally, we evaluate and analyse model's performance and show that for simplicity, existing schemes impractically assume single MF (i.e., higher SE and ML) compared to fixed-grid networks, thereby ignoring the flexible nature of EONs.